IMPLEMENTASI STRATEGI PUBLICITY BERBASIS PROYEK DALAM PEMBELAJARAN SEKOLAH DASAR UNTUK MENINGKATKAN KREATIVITAS DAN LITERASI DIGITAL SISWA SDIT MULTAZAM PAMEKASAN - iswadi (CV. Abid Abadi Jaya, 2025)
This study aims to improve students’ creativity and digital literacy through the implementation of a project-based publicity strategy in learning at SDIT Multazam Pamekasan. The study employed Classroom Action Research (CAR) using the Kemmis and McTaggart model, conducted in two cycles consisting of planning, action, observation, and reflection stages. The research subjects were 54 students from grades IV and V. Data were collected through observation, tests, questionnaires, and documentation. The results showed a significant improvement in students’ creativity, increasing from an average of 47% in the first cycle to 82% in the second cycle. In addition, students’ product assessment scores improved from 74% to 85%. The implementation of the project-based publicity strategy encouraged students to be more active, creative, and capable of utilizing digital technology to produce and publish their work. Therefore, this strategy is effective in enhancing creativity and digital literacy among elementary school students.